Complexities of Benchmarking - Juvela, Anssi (My University, 2023)
EN In this master’s thesis my central goal is to examine benchmarking as an academic phenomenon and moreover how principles of complexity thinking can be adapted into benchmarking and comparison of public governments. An overview of the history and ideology behind contemporary benchmarking boom is also laid. Focus in the case-study section is on two worldwide surveys: the Happiness Index and the InCiSE. My aim is to analyze the techniques used in both of the studies consisting of their advantages and disadvantages. One aspect is how to perceive the vast amounts of comparative data that where the answer lies in complexity thinking. On a more practical level the thesis discusses certain political aspects related to happiness and complexity. One key element in the thesis is also to scrutinize why Finland did so well in both of the benchmarking surveys. FI Tässä Pro Gradu-tutkielmassa keskeisenä tavoittenani on tutkia vertailukehittämistä tieteellisenä ilmiönä. Sen lisäksi tarkastelen sitä, kuinka kompleksisuusajattelun periaatteita voitaisiin soveltaa vertailukehittämiseen ja julkishallintojen vertaamiseen. Työ sisältää katsauksen vallitsevan vertailukehittämis-innon taustalla olevaan historialliseen ja ideologiseen kehitykseen. Painopiste tapaustutkimus-osiossa on kahdessa kansainvälisessä kyselytutkimuksessa: Onnellisuusideksissä ja InCiSEssä. Tavoitteenani on analysoida kummassakin tutkimuksessa käytettyjä tekiikoita vahvuuksineen ja kehityskohteineen. Eräs tutkielman keskeisistä näkökulmista on se, kuinka kompleksisuus-ajattelun avulla vertailujen kautta saatuja valtavia tietomääriä voitaisiin entistäkin paremmin käsitellä. Käytännöllisempien tulokulmien osalta tutkielmassa käsitellään tiettyjä poliittisluonteisia näkökohtia liittyen onnellisuuteen ja kompleksisuuteen. Punaisena lankana on myös tarkastella Suomen hyvää menestystä molemmissa vertailukehittämis-tutkimuksissa.
Keywords: benchmarking; public administration; organisations (systems); leadership (activity); administration (systems of a society); complexity; enterprises; comparison; international comparison; universities; fi=Julkisjohtaminen|en=Public Management|; fi=Hallintotieteiden maisteriohjelma|en=Master's Programme in Administrative Sciences|